(untitled) (Práxis Educativa, 2024)
This paper presents the results of an investigation aimed at analyzing Pierre Bourdieu’s epistemethodological contributions to research in the field of Education Policy. The theoretical framework was based on the ideas of Bourdieu and his commentators. The research involved an epistemological study of Bourdieu’s works that deal more specifically with epistemological and methodological issues, and studies that sought to indicate Bourdieu’s contributions to the education policy research in Brazilian and foreign literature. It is argued that Bourdieu developed a wide range of resources for scientific research, resulting in substantial epistemethodological contributions that can be extended to the theoretical and epistemological debates of research in the field of Education Policy. The results show that: a) among the primary epistemethodological contributions to the theoretical and epistemological debates of research in the field of Education Policy, the following stand out: relational thinking and epistemic reflexivity; b) the concepts most expressively observed as contributing to research in education policy are the tools of thought: field, habitus, capital and practice; c) the application of the Bourdieusian contributions has enabled theoretical developments in the field of Education Policy in at least two dimensions: to improve the processes involved in conducting research in the field of Education Policy; and to broaden the understanding of the education policy cycle, that is the processes of policy formulation and implementation. Keywords: Pierre Bourdieu. Epistemology. Education policy.